ARGONAUT-I: Activity of Cefiderocol (S-649266), a Siderophore Cephalosporin, against Gram-Negative Bacteria, Including Carbapenem-Resistant Nonfermenters and Enterobacteriaceae with Defined Extended-Spectrum β-Lactamases and Carbapenemases - Jacobs, Michael R. (Antimicrob Agents Chemother, 2018)
The activity of the siderophore cephalosporin cefiderocol is targeted against carbapenem-resistant Gram-negative bacteria. In this study, the activity of cefiderocol against characterized carbapenem-resistant Acinetobacter baumannii complex, Stenotrophomonas maltophilia, Pseudomonas aeruginosa, and Enterobacteriaceae strains was determined by microdilution in iron-depleted Mueller-Hinton broth. The MIC(90)s against A. baumannii, S. maltophilia, and P. aeruginosa were 1, 0.25, and 0.5 mg/liter, respectively. Against Enterobacteriaceae, the MIC(90) was 1 mg/liter for the group harboring OXA-48-like, 2 mg/liter for the group harboring KPC-3, and 8 mg/liter for the group harboring TEM/SHV ESBL, NDM, and KPC-2.